Male Migration to Middle East and the Impact on the Family Some Evidence from Kerala - Leela Gulati (ECONOMIC AND POLITICAL WEEKLY, 1983)
This paper is divided into two parts. Part I gives a brief background of the extent and pattern of recent migration to the Middle East from India as a whole and from the State of Kerala in particular. In Part II, the paper goes on to discuss the impact of this migration, male dominated as it has been, on the family as such. The paper concludes with some general observations.